The Learning Effects of Monitoring - Campbell, Dennis; Epstein, Marc J.; Martinez-Jerez, F. Asis (The Accounting Review, 2011)
ABSTRACT This study investigates the relationship between monitoring, decision making, and learning among lower-level employees. We exploit a field-research setting in which business units vary in the “tightness” with which they monitor employee decisions. We find that tighter monitoring gives rise to implicit incentives in the form of sharp increases in employee termination linked to “excessive” use of decision-rights. Consistent with these implicit incentives, we find that employees in tightly monitored business units are less likely than their loosely monitored counterparts to: (1) use decision-rights; and (2) adjust for hard information, in the form of historical performance data, in their decisions. These decision-making patterns are associated with large and systematic differences in learning rates across business units. Learning is concentrated in business units with “loose monitoring” and entirely absent in those with “tight monitoring.” The results are consistent with an experimentation hypothesis in which tight monitoring of decisions leads to more control but less learning. Data Availability: The data used in this study cannot be made publicly available due to confidentiality agreements with the participating organization.